Antimicrobial Stewardship Programmes in Community Healthcare Organisations in England: A Cross-Sectional Survey to Assess Implementation of Programmes and National Toolkits - Diane Ashiru-Oredope; Anne Doble; Mary Richard Akpan; Sejal Hansraj; Nada Atef Shebl; Raheelah Ahmad; Susan Hopkins (MDPI AG, 2018)
Objective: The aim of this study was to assess antimicrobial stewardship activities in Community Healthcare Organisations (CHOs) with focus on the implementation of the two national antimicrobial stewardship toolkits, TARGET (Treat Antibiotics Responsibly, Guidance, Education, Tools) and SSTF (Start Smart, then Focus). The study utilised a web-based survey comprising 34 questions concerning antimicrobial policies and awareness and implementation of antimicrobial stewardship toolkits. This was distributed to pharmacy teams in all 26 CHOs in England. Twenty CHOs (77%) responded. An antimicrobial stewardship (AMS) committee was active in 50% of CHOs; 25% employed a substantive pharmacist post and 70% had a local antibiotic policy. Fourteen of the responding CHOs were aware of both AMS toolkits, five organisations were aware of either SSTF or TARGET, and one organisation was not aware of either toolkit. Of the organisations aware of SSTF and TARGET, eight had formally reviewed both toolkits, though three had not reviewed either. Less than half of the respondents had developed local action plans for either toolkit. National guidance in England has focused attention on initiatives to improve AMS implementation in primary and secondary care; more work is required to embed AMS activities and the implementation of national AMS toolkit recommendations within CHOs.